(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In today’s technology era, programming is more essential than ever. Python and C++ are the most widely used programming languages. Python, the most popular programming language of the twenty-first century, is a higher-level object-oriented language, while C++ (the language that powers most operating systems) is a lower level object-oriented language. Python and C++ are compared in this article. This book covers an introduction to various languages, memory management techniques, and reasons for their program execution speed. Furthermore, this study looked at the execution time and memory requirements of a variety of algorithms in both languages, comparing the best, average, and worst situations in each language. Furthermore, they are compared in terms of their benefits and drawbacks. C++ is faster than Python in terms of execution speed, according to the findings, but Python is a better option for beginners due to its simplicity. Aside from that, the language should be selected depending on the project type in order to get the best results. Programmers play a crucial role in computing. C/C++, Python, and Java are the most common languages. Beginning programming classes often utilize C++ and Java. Python has grown in popularity as an introductory programming language due to a variety of reasons. As an entry-level programming language, C, C++, Java, and Python were compared. More students selected Python over C++ because of its simpler pseudo-code syntax, better learning environment, and greater abstraction.